Answer:
Step-by-step explanation:
There are a couple of factored forms that are used here:
(a +b)² = a² +2ab +b² . . . . the sign of "2ab" will match the sign of b
a² -b² = (a -b)(a +b)
__
Part A:
Since this trinomial is known to be a perfect square, you can find the binomial(s) by looking at the roots of the first and last terms.
√(4a²) = 2a
√25 = 5
The factoring is ...
4a² -20a +25 = (2a -5)²
__
Part B:
This is the difference of perfect squares, so the terms of the factors can be found as in the previous part.
√(9a²) = 3a
√(16b²) = 4b
Using the above factored form, we have ...
9a² -16b² = (3a -4b)(3a +4b)